Credit Position and Retail Firm Operational Efficiency: Evidence from China - Zhang, Yue (2021)
The relationship between operational efficiency and credit position has not received significant attention despite credit position being an important factor in retail firms. In economies where the access to finance is limited, private firms resort to trade credit, and firms rely on credit position to secure trade credit, hence consequently the improving the operations of the firm. The operational efficiency of Chinese companies is not strong, and it is characterized by a number of aspects including low innovation ability, and poor product quality leading to the question; does credit position have a negative or positive influence on operational efficiency of retail firms in China? To answer the question, this research sought to explore the relationship between credit position and operational efficiency of retail firms in China. Rather than using operational efficiency ratios, the study adopts a non-parametric measure of operational efficiency namely the Data Envelopment Analysis. The study further employs bootstrapped Tobit regression model to establish the relationship between credit position and operational efficiency. The study found that credit position has significant beneficial effects on the efficiency of Chinese retail companies. The study finds that the beneficial effects of credit position increase with increase in firm size. The study concludes that credit position creates avenue for more liquidity which the firm can leverage to smoothen the operations, whether through improving technologies, or increasing inventory materials, or paying distribution and marketing expenses among others.